Developing a structural model of adherence to treatment based on resilience with the mediation of perceived stress in patients with rheumatoid arthritis - Bakhshandeh, Fatemeh; Rezaei Jamalooei, Hassan; Salesi, Mansour (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The present study aimed to develop a structural model of treatment adherence based on resilience with the mediation of perceived stress in patients with rheumatoid arthritis. Methods and Materials: Methodologically, this research was descriptive-survey and used structural equation modeling. The statistical population included patients with rheumatoid arthritis in the city of Isfahan. Participants were individuals with rheumatoid arthritis who had been referred to healthcare centers in Isfahan and had experienced the disease for at least one year. Data were collected using the Treatment Adherence Questionnaire by Ziaei (2010), the Connor-Davidson Resilience Scale (CD-RISC), Antonovsky’s Sense of Coherence Scale (1993), Cohen, Kamarck, and Mermelstein’s Perceived Stress Scale (1983), and the Difficulties in Emotion Regulation Scale (DERS) by Gratz and Roemer (2004). The data were analyzed using structural equation modeling and Amos 26 software. Findings: The results confirmed the indirect effect of resilience on treatment adherence through the mediation of perceived stress (p < .01). Conclusion: The findings demonstrated that the structural model of treatment adherence based on resilience with the mediation of perceived stress in patients with rheumatoid arthritis had a good fit.